ROLE OF RETURBT IN TA BLADDER TUMOURS OUR EXPERIENCE IN TERTIARY HEALTH CARE. - Dr. Yasir Iqbal Lone; Dr. Akansha Jain; Dr. Khushbu Girdher; Dr. Annam Qayoom (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Bladder cancer is one of the most frequently diagnosed malignancies of the urinary tract, with non-muscle invasive bladder cancer (NMIBC) constituting nearly 75% of all cases. Among these, Ta bladder tumors represent a subset confined to the urothelium without lamina propria invasion. While transurethral resection of bladder tumor (TURBT) is the primary diagnostic and therapeutic modality, studies indicate a substantial risk of residual tumor presence after initial resection. Re-TURBT (repeat TURBT) has been advocated to ensure complete tumor removal, improve staging accuracy, and reduce recurrence rates. However, its necessity in Ta tumors remains a topic of debate, particularly in resource-limited settings. Aim:  This study aims to evaluate the role of re-TURBT in Ta bladder tumors at Hamdard Institute Of Medical Sciences, New Delhi , by analyzing its impact on residual tumor detection, pathological upstaging, recurrence rates, and treatment modifications.  Methods:  A prospective study was conducted in the department of surgery at Hamdard Institute Of Medical Sciences, New Delhi from Dec 2023 to Jan 2025. A total of 120 patients with newly diagnosed Ta bladder tumors were included. All patients underwent an initial TURBT, followed by a scheduled re-TURBT within 4–6 weeks. Histopathological outcomes, presence of residual disease, upstaging rates, and recurrence patterns were analyzed. Statistical analysis was performed using SPSS software, with p-values